Arthus And The Earthworms - Mercier,Johanne (London Phoenix Yard, 2013)
"I'm Arthur and I'm seven, and starting tomorrow I've got a new job: I'm going to be selling earthworms. I started getting interested in worms because of my duck. He lives at my grandparents' house and worms are his favourite food. When I really want to give him a treat, we go worm-hunting together. It rained a lot on Sunday, so we found hundreds! This gave my grandfather an idea... Series description: Arthur is a seven-year-old boy who is brilliant at being a seven-year-old-boy. When Arthur visits his grandparents' house by the lake, more often than not, he becomes entangled in a new adventure, which he must solve with the help of his pet duck and useless dog and hopefully without too much help from eccentric Cousin Eugene. These are witty stories full of understated humour and populated by quirky yet recognisable characters, and narrated by Arthur who has the rational worldview that comes exclusively from being seven-years-old" -- Publisher description
Keywords: English Story Book